Alagille Syndrome and Wilson Disease in Siblings: A Diagnostic Conundrum. (2012) - Amson, Meghan; Lamoureux, Esther; Hilzenrat, Nir; Tischkowitz, Marc
Abstract : The authors describe two siblings, each with a different, rare genetic condition that affects liver function. The index case, the 18-year-old asymptomatic brother of a young man recently diagnosed with Wilson disease, presented for Wilson disease screening and was also found to have abnormal liver function suggestive of cholestasis. However, ceruloplasmin level, 24 h urine copper concentration and liver synthetic function were normal. Further hepatic investigations and genetic mutation analysis were performed, ultimately leading to a diagnosis of Alagille syndrome. He was treated with ursodiol, which resulted in normalization of his liver function tests. Subsequently, he was found to be a carrier for a mutation in the Wilson disease gene, ATP7B . In the present report, the potential implications of being a heterozygote for Wilson disease in the context of Alagille syndrome are discussed. Also stressed is that care must be exercised by the clinician when diagnosing family members who may present with two different disorders closely mimicking one another.